2016
DOI: 10.1016/j.jhazmat.2016.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Salisbury biochar did not affect the mobility or speciation of lead in kaolin in a short-term laboratory study

Abstract: Salisbury biochar (produced from British broadleaf hardwood) with two different particle sizes (≤ 2 mm and ≤ 0.15 mm) was applied on a kaolin with three different lead (Pb 2+ ) contamination levels (50 mg/kg, 300 mg/kg and 1000 mg/kg) at the dosage of 1% in w/w. The short-term impact of biochar on the mobility and speciation of Pb 2+ in the kaolin was investigated using attenuation periods of 1, 7and 28 days. This paper suggests the inefficiency of biochar treament on heavy-metal contaminated clay-rich so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 32 publications
(37 reference statements)
1
18
0
Order By: Relevance
“…The volatile matter content, total ash content and elementary contents (C, H, N, O) of SB are determined based on UKBRC standard. Other properties for SB and selected physicochemical properties of WSP700, RH700 and SWP550 can be found from the previous studies (Shen et al, 2015(Shen et al, , 2016a(Shen et al, , 2016b(Shen et al, , 2017 and are also shown in Table 1.…”
Section: Biocharmentioning
confidence: 99%
See 2 more Smart Citations
“…The volatile matter content, total ash content and elementary contents (C, H, N, O) of SB are determined based on UKBRC standard. Other properties for SB and selected physicochemical properties of WSP700, RH700 and SWP550 can be found from the previous studies (Shen et al, 2015(Shen et al, , 2016a(Shen et al, , 2016b(Shen et al, , 2017 and are also shown in Table 1.…”
Section: Biocharmentioning
confidence: 99%
“…Salisbury biochar (SB) was obtained from Southern Woodland Products (Salisbury, UK). It was produced from British broadleaf hardwood at a pyrolysis temperature of 600 ºC in a retort with a residence time of 13.5 h. SB was previously applied to a field contaminated site in the UK and exhibited excellent performance in immobilising Ni 2+ and Zn 2+ in a sandy soil throughout a three-year study (Shen et al, 2016a). In contrast, SB did not affect the mobility or speciation of Pb 2+ in kaolin in a short-term study (Shen et al, 2016b).…”
Section: Biocharmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, soil type and clay content could often play an important role in metal immobilisation by biochar. For example, Shen et al (2016) suggested that the biochar-amended clayey soils was not satisfactory for adsorption of Pb. Therefore, the effect might become more prominent in a light-textured soil as used in the present study.…”
Section: Heavy Metal Immobilisation By Biocharmentioning
confidence: 99%
“…The recoveries of Pb 2+ from OSDCs were within 74.15-87.26%. Shen et al (2016) conducted sequential extraction to determine the speciation of Pb 2+ on biochar treated soil. The recoveries of the Pb 2+ were within 61.50-97.28%, which were comparable to the recovery of Pb 2+ and Cd 2+ in this study.…”
Section: Sequential Extraction Resultsmentioning
confidence: 99%